Me and My VE, Part 5: Applications in Human Factors Research and Practice. (September 2018) - Spain, Randall; Goldberg, Benjamin; Hansberger, Jeffrey; Griffith, Tami; Flynn, Jeremy; Garneau, Christopher; Shorter, Paul; Sinatra, Anne; Key, Phillip; Finseth, Tor
Recent advances in technology have made virtual environments, virtual reality, augmented reality, and simulations more affordable and accessible to researchers, companies, and the general public, which has led to many novel use cases and applications. A key objective of human factors research and practice is determining how these technology-rich applications can be designed and applied to improve human performance across a variety of contexts. This session will demonstrate some of the distinct and diverse uses of virtual environments and mixed reality environments in an alternative format. The session will begin with each demonstrator providing a brief overview of their virtual environment (VE) and a description of how it has been used to address a particular problem or research need. Following the description portion of the session, each VE will be set-up at a demonstration station in the room, and session attendees will be encouraged to directly interact with the virtual environment and ask demonstrators questions about their research and inquire about the effectiveness of using VE for research, training, and evaluation purposes. The overall objective of this alternative session is to increase the awareness of how human factors professionals use VE technologies and increase the awareness of the capabilities and limitations of VE in supporting the work of HF professionals.